The Use of Management by Objectives by the Departments of Public Relations in Jordanian Universities and its Impact on their Job Performance: A Survey Study - Shatnawi, Ghalib; Mohammad, Ahmmad S. (Dirasat: Human and Social Sciences, 2023)
This study aimed to examine and identify to what extent could public relations departments in Jordanian universities apply and practice the administration with objectives and its reflection on these departments` employees` job performance. This study relied on the descriptive approach and it targeted comprehensively all 49 employees working in the P.R. departments of all Jordanian universities in the northern rejoin, the employees` responses were collected by using a questionnaire tool. The main results revealed by this study are, practicing management by objectives in the public relations departments of Jordanian universities and practicing the principle of participation are moderately practiced, while the principle of setting goals to be practiced at a high degree, the principle of supporting senior management and oversight is practiced at a moderate level, but the principle of evaluation is practiced at a low level. The study also reveals that employees` functional performance was high. The study also showed the existence of a statistically significant relationship between practicing the principle of participation and job performance. On the other hand, there was no statistically significant relationship between the principles of setting goals, support for senior management, oversight, evaluation, and job performance. The study also reveals that there were statistically significant differences between the type of university and job performance.